Wilbert I. Slemmons, Laws and Ordinances of the City of Peoria Illinois 653 (1892) - (:unkn) unknown (My University, 1891)
§ 1670, § 54: Prohibited discharging any air-gun, "bean-shooter," "nigger-killer", or any other instrument or machine, from which a missile is discharged or hurled, under a penalty of not less than twenty-five dollars for every offense.
Keywords: DISCHARGE